THE EXISTENCE OF AEDESAEGYPTI MOSQUITO BREEDING BASE BASED ON GEOGRAPHIC INFORMATION SYSTEMS IN DARULIMARAHDISTRICT, ACEH BESARREGENCY - Sofia, Sofia; Kartini (Aceh Sanitation Journal, 2022)
Efforts to control Dengue Hemorrhagic Fever (DHF) require complete and accurate information. The spread of the virus can be seen from the perspective of spatial information (geospatial), one of the main components is a picture of the earth both in whole or in part made in analog or digital format. Darul Imarah districtis one of the endemic districts of DHF with 32 cases in 2017. The distribution of cases is made in the form of spatial mapping.The aim of this research is to map the existence of Aedesaegypti breeding place based on geographic information system (GIS) in DarulImarahDistrict. This research method is descriptive observational survey using geographic information system modeling through spatial analysis. The research subject is the data of dengue hemorrhagic fever cases in 2017 and Aedesaegypti breeding places in the case home environment. Data analysis was performed descriptively, then presented with spatial analysis.The results of the analysis note that the existence of breeding places and dense housing has the potential for DHF. The home environment of DHF patients found less than 100 meters in the presence of breeding places. Through the use of this information, it is expected that the Puskesmas and village servants can move the community's participation in the practice of eradicating mosquito nests so that